2018
DOI: 10.1155/2018/7451946
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Markers for Nonspecific Inflammatory Bowel Diseases

Abstract: The nonspecific inflammatory bowel diseases (IBD) represent a heterogeneous group of chronic inflammatory disorders of the gastrointestinal tract, and Leśniowski-Crohn's disease (CD) and ulcerative colitis (UC) are among the two major clinical forms. Despite the great progress in understanding the pathogenesis of these diseases, their etiology remains unclear. Genetic, immune, and environmental factors are thought to play a key role. The correct diagnosis of nonspecific inflammatory bowel diseases as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 90 publications
0
20
0
3
Order By: Relevance
“…The misdiagnosis rate for IBD, including a change in diagnosis from IBD to a non-IBD diagnosis or vice-versa, is reported to be as high as 23.5% (Table 1) [26]. In certain cases, where it is impossible for the attending physician to reach a final diagnosis of UC or CD, the designation of indeterminate colitis (IC) is used, accounting for up to 15% of IBD patients [61]. Opinions vary on the classification of IC, as some physicians classify it as a distinct autonomic pathoclinical unit with similar etiology to UC or CD, while others use the IC classification as a temporary diagnosis and rely on additional diagnostic testing over time to establish a diagnosis of CD or UC [61].…”
Section: Clinical Manifestation Diagnosis and Management Of Inflmentioning
confidence: 99%
“…The misdiagnosis rate for IBD, including a change in diagnosis from IBD to a non-IBD diagnosis or vice-versa, is reported to be as high as 23.5% (Table 1) [26]. In certain cases, where it is impossible for the attending physician to reach a final diagnosis of UC or CD, the designation of indeterminate colitis (IC) is used, accounting for up to 15% of IBD patients [61]. Opinions vary on the classification of IC, as some physicians classify it as a distinct autonomic pathoclinical unit with similar etiology to UC or CD, while others use the IC classification as a temporary diagnosis and rely on additional diagnostic testing over time to establish a diagnosis of CD or UC [61].…”
Section: Clinical Manifestation Diagnosis and Management Of Inflmentioning
confidence: 99%
“…These peptides are expressed by both immune and structural cells, and expression levels of some CHDP are enhanced in presence of infection or inflammatory challenge. Several studies have demonstrated altered levels of CHDP cathelicidin and calprotectin (a complex of subunits S100A8 and S100A9) in various chronic inflammatory diseases including rheumatoid arthritis (RA), chronic obstructive pulmonary disease (COPD), asthma, inflammatory bowel disease (IBD) and atherosclerosis (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, alteration of abundance of specific CHDP in chronic inflammatory diseases has not been completely defined.…”
Section: Introductionmentioning
confidence: 99%
“…1A,B, Table 1B). Increased MPV is associated with inflammatory disorders, including IBD [13,14]. IL-10 is a key inflammatory suppression cytokine associated with IBD and is an important developmental switch in monocyte -> macrophage differentiation, acting through the Stat3 transcription factor, its known effector [22,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…MVP, ESR, and CRP parameters of CBC-D have each been reported as statistically-supported indicators of IBD. [13,14] CBC monocyte count is also indicator of inflammation [15]. CD14, LPS, Cortisol, and IL-10 are reported indicators of immune response or inflammatory suppression, respectively.…”
Section: Introductionmentioning
confidence: 99%